SEASONAL VARIATIONS OF CERTAIN MAJOR ZOOPLANKTON GROUPS AROUND PANGGANG ISLAND, NORTH-WEST OFF JAKARTA - Arinardi, O. H. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1978)
Seasonal and annual variations of the composition of zooplankton in the water around Panggang Island were studied from May 1971 to April 1973. Temperature and salinity of the water and the abundance of zooplankton were assumed to be affected by the monsoon. It was usually found that the abundance of zooplankton in this area coincided with or occurred after the heavy rainfall. The occurrence of many zooplankton groups in each season did not greatly change, but the intensity of total number were vary in certain groups. The pattern of the annual variation of the zooplankton number was nearly regular in the two years of investigations. The major groups of zooplankton observed during this investigations were also discussed. In general the zooplankton of the water of Panggang Island were typically neritic. Some bigger species of copepods were even less than in the Java Sea.